2020
DOI: 10.1016/j.neuron.2020.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Precision Calcium Imaging of Dense Neural Populations via a Cell-Body-Targeted Calcium Indicator

Abstract: Highlights d One-photon calcium imaging of brain activity can suffer from neuropil crosstalk d Targeting GCaMPs to the cell body reduces neuropil crosstalk d One-photon imaging of somatic GCaMP reduces artifactual spikes and correlations d Somatic GCaMPs can be used in multiple species, such as mice and zebrafish

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(65 citation statements)
references
References 68 publications
1
57
0
Order By: Relevance
“…LNvs receive synaptic input from larval photoreceptors and exhibit robust calcium responses upon light stimulation 41 . Using a genetically encoded calcium indicator GCaMP7f 50 , we measured light-evoked calcium increases in the axonal terminal region of the LNvs (Fig. 3d ).…”
Section: Resultsmentioning
confidence: 99%
“…LNvs receive synaptic input from larval photoreceptors and exhibit robust calcium responses upon light stimulation 41 . Using a genetically encoded calcium indicator GCaMP7f 50 , we measured light-evoked calcium increases in the axonal terminal region of the LNvs (Fig. 3d ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, red Ca 2+ sensors R-GECO [ 86 , 87 ] and RCaMP [ 87 , 88 ] were developed from cp-mApple and cp-mRuby, respectively. The Ca 2+ sensors were continuously improved; thus, we can currently monitor dynamic changes of intracellular Ca 2+ levels in living animal as well as live cells [ 89 , 90 , 91 , 92 , 93 ].…”
Section: Sensing Strategies Of Fp-based Biosensorsmentioning
confidence: 99%
“…In these in vivo instances, using confocal laser scanning microscopy would have likely been inadequate, as comparatively, 2PI significantly reduces photobleaching, increases cell viability, and allows for deeper tissue penetration [69]. Furthermore, it has been reported that, when imaging neuronal cells specifically, single-photon microscopy suffers from increased interference by neuropil and decreased signal-to-noise ratio compared to 2PI [70].…”
Section: Two-photon Imagingmentioning
confidence: 99%